Cytotoxic effects of metal complexes of biogenic polyamines. I. Platinum(II) spermidine compounds: prediction of their antitumour activity - Marques, M. P. M. (2002)
Cytotoxicity and cell growth inhibition studies were performed for three distinct polynuclear platinum(II) complexes of spermidine, which showed to have significant cytotoxic and antiproliferative properties on the HeLa cancer cell line. The chemical environment of the metal centres in the drugs, as well as the coordination pattern of the ligand, were found to be strongly determinant of their cytotoxic ability. In the light of the results gathered, the most effective anticancer compound among the ones tested (IC50=5 [mu]M) was found to be the one displaying three difunctional (PtCl2N2) moieties ((PtCl2)3(spd)2). Both the cytotoxic activity and the antiproliferative properties of the complexes studied showed to be irreversible for all the concentrations tested.